Daily distribution of carbohydrate, protein and fat intake in elite youth academy soccer players over a 7-day training period - Naughton, R. J.; Drust, B.; O`Boyle, A.; Morgans, R.; Abayomi, J.; Davies, I. G.; Morton, J. P.; Mahon, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
While traditional approaches to dietary analysis in athletes have focused on total daily energy and macronutrient intake, it is now thought that daily distribution of these parameters can also influence training adaptations. Using 7-day food diaries, we quantified the total daily macronutrient intake and distribution in elite youth soccer players from the English Premier League in U18 (n = 13), U15/16 (n = 25) and U13/14 squads (n = 21). Total energy (43.1 ± 10.3, 32.6 ± 7.9, 28.1 ± 6.8 kcal·kg-1·day-1), CHO (6 ± 1.2, 4.7 ± 1.4, 3.2 ± 1.3 g·kg- 1·day-1) and fat (1.3 ± 0.5, 0.9 ± 0.3, 0.9 ± 0.3 g·kg-1·day-1) intake exhibited hierarchical differences (p < .05) such that U13/14 > U15/16 > U18. In addition, CHO intake in U18s was lower (p < .05) at breakfast, dinner and snacks when compared with both squads but no differences were apparent at lunch. Furthermore, the U15/16s reported lower relative daily protein intake than the U13/14s and U18s (1.6 ± 0.3 vs. 2.2 ± 0.5, 2.0 ± 0.3 g·kg-1). A skewed distribution (p < .05) of daily protein intake was observed in all squads, with a hierarchical order of dinner (~0.6 g·kg-1) > lunch (~0.5 g·kg-1) > breakfast (~0.3 g·kg-1). We conclude elite youth soccer players do not meet current CHO guidelines. Although daily protein targets are achieved, we report a skewed daily distribution in all ages such that dinner > lunch > breakfast. Our data suggest that dietary advice for elite youth players should focus on both total daily macronutrient intake and optimal daily distribution patterns.